Resistance exercise with blood flow restriction elicits perceptual responses similar to high-load resistance exercise in women with type 2 diabetes: a crossover and randomized study - Ana Beatriz Alves Martins; Nailton José Brandão de Albuquerque Filho; Marina Gonçalves Assis; Victor Sabino de Queiros; Arthur Wagner da Silva Rodrigues; Eliete Samara Batista dos Santos; Breno Guilherme de Araújo Tinôco Cabral; Júlio Cesar Gomes da Silva; Gabriel Rodrigues Neto (Instituto Brasileiro de Pesquisa e Ensino em Fisiologia do Exercício, 2023)
Introduction: Physical training with blood flow restriction (BFR) may provide health benefits for people with diabetes. However, the negative effects cannot be overlooked. Aim: This study aimed to analyze the acute effect of resistance exercise BFR on the rating of perceived exertion (RPE) and subjective perception of pain in untrained women with type 2 diabetes (T2DM). Methods: Ten untrained women with T2DM (56.9 ± 7.4 years; diagnostic time: 10.6 ± 4.1 years) participated in this study. Participants attended a local gym for four non-consecutive days. Initially, predictive values of one maximum repetition (1RM) and arterial occlusion pressure (AOP) were measured. In random order, second, third, and fourth visits were allocated to the following: high-load (HL) exercise (65% 1RM; three sets of 10 repetitions), low-load (LL) exercise (20% of 1RM; three sets of 15 repetitions), and LL exercise with BFR (LL+BFR) (20% 1RM; three sets of 15 repetitions; 50% of AOP). RPE and pain perception were assessed immediately after each set. RPE increased significantly over the sets for all exercise protocols (p<0.05). The perception of pain increased significantly throughout the sets only in the HL and LL+BFR exercise protocols (p<0.05). LL+BFR and HL exercises showed similar RPE values and pain perception, but significantly higher than the LL exercise (p<0.05). We conclude that LL resistance exercise with BFR promotes perceptual responses similar to traditional HL exercise in untrained women with T2DM.